Fungi Associated with Freshly Harvested Corn Grains in Duhok Governorate - Raed A. Haleem; Khdija A. Saido; Samir Kh. Abdullah; Sahad N. Aldeen; Ihssan M. Waesi (Science Journal of University of Zakho, 2013)
Freshly harvested grains of five corn hybrids collected from Duhok governorate were screened for their associated mycoflora using agar plate and blotter methods. The percentage occurrence of the isolated fungi was varied with respect to corn hybrid. Aspergillus niger, A. flavus and Rhizopus spp were the most frequently detected species. From 4 to 70% of grains were infected with fungi and their percentage germination ranged from 53 to 98%. The species composition and percentage germination of grains differed among corn hybrids. A total of 48 strains of A. flavus obtained from different hybrids were tested for their aflatoxigenic potential. The positive strains ranged from 70 to 100%.